Directives Illocutionary and Perlocutionary Acts Found in The Girl Who Fell Beneath the Sea by Axie Oh - Ferica Tasya Arvanti; Sujana Sujana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This research aims to identify the types of directives illocutionary acts by Searle and perlocutionary acts by Austin, that occurred in the novel The Girl who Fell Beneath the Sea by Axie Oh. The data for this research were obtained using a descriptive-qualitative method. The data of this study are taken from 291 utterances that featured directives illocutionary acts. The result of this research showed seven out of eleven types of directives illocutionary acts were found; asking (184), begging (11), commanding (8), demanding (29), ordering (36), requesting (8), and warning (15). Furthermore, the researcher also found that after receiving directives illocutionary acts from the speaker, there were successful and unsuccessful perlocutionary acts from the interlocutor.